Genetic variability of chakkarakolli (Gymnema sylvestre R. Br.) in Kerala assessed using morphological and biochemical markers - Smita Nair and R. Keshavachandran (Journal of Tropical Agriculture 44 (1-2): 64-67, 2006, 2006)
Gymnema sylvestre R. Br. is a native medicinal plant valued for its antidiabetic property. The major bioactive constituents of Gymnema are a group of saponins. In the present study, morphological and biochemical markers were employed for characterizing 93 germplasm accessions of Gymnema representing different geographical regions of Kerala. Seven vegetative traits and total saponin concentrations in the leaves were studied on three-year-old plants. The results indicate high variations in morphological and biochemical characters. Saponin concentration ranged from 0.6 per cent for `Pambadi' to 5.4 per cent for `Kottayi.